Design-driven innovation no processo de desenvolvimento de novos produtos: o design como agente de inovação de significados - Casenote, Igor Escalante (Universidade do Vale do Rio dos Sinos, 2011)
There are two key factors that defines the contemporary Western society: the first one is the search for unique identity construction before the mass and the emotional completion through the acquiring of meaning imbued goods, a very evident feature of the product design; the other one relates to the growing consumer demand for novelty and its increasing speed of aging given the technology escalation, putting producers into a permanent condition of alertness, as the need of continuous development of new products rules the companies agenda. Replying to this scenario, emerges the design-driven innovation approach, with the assumption that the watching, identifying and captu ring of even the smallest signs of social transformation enables the company to anticipate the demand for products, enabling the delivery of formerly unthinkable solutions to consu mers. In order to study the regional context applicability of this originally European a pproach, it was developed a single case study inside a house wares manufacturer, whose data were obtained through interviews and secondary documents, later analyzed via content analysis. The extracted results indicate lack of proximity to the design-driven innovation proposal, demonstrating the need of a joint effort between the several functional layers of the company in the task of spreading the innovation culture.
Keywords: Design; Inovação; Tendências; Novos produtos; Innovation; Trends; New products; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial